On the Interplay Between Monetary Policy and Macroprudential Policy: A Simple Analytical Framework - Øistein Røisland (Norges Bank, 2017)
The paper provides a simple analytical framework for analyzing the interplay between monetary policy and macroprudential policy. Three questions are analyzed: (i) Under which assumptions is coordination necessary to implement an optimal policy mix? (ii) Are the two policy instruments substitutes or complements, i.e. should they move in opposite or the same direction as response to a shock? (iii) Can "leaning against the wind" in monetary policy lead to a negative inflation bias?
hdl:11250/2495559
Keywords: E52; E58; E61; 330; monetary policy; macroprudential policy; coordination